2018
DOI: 10.32607/20758251-2018-10-3-11-22
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Regulation in Autoimmune Diseases

Abstract: Antibody-independent B cell effector functions play an important role in the development and suppression of the immune response. An extensive body of data on cytokine regulation of the immune response by B lymphocytes has been accumulated over the past fifteen years. In this review, we focused on the mechanisms of inflammatory response suppression by subpopulations of regulatory B cells in health and autoimmune pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 92 publications
1
14
0
Order By: Relevance
“…This is consistent with several reports on the impact of IL-33 in inducing Breg cells in other animal models [17,35]. The beneficial role of Breg cells in suppressing inflammation and limiting the development of autoimmune diseases, including SLE, has been known [17,36,37]. For example, CD1d hi CD5 + Breg cells contributed to the prolonged survival and suppressed lupus progression in NZB/W F1 mice [38].…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with several reports on the impact of IL-33 in inducing Breg cells in other animal models [17,35]. The beneficial role of Breg cells in suppressing inflammation and limiting the development of autoimmune diseases, including SLE, has been known [17,36,37]. For example, CD1d hi CD5 + Breg cells contributed to the prolonged survival and suppressed lupus progression in NZB/W F1 mice [38].…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have found that regulatory B (Breg) cells can contribute to the suppression of inflammation and support the differentiation of Tregs ( 24 25 ). IL-10-producing regulatory B (B10) cells, a subset of Breg cells, counteract inflammatory diseases such as collagen-induced arthritis and colitis ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…IPSE/alpha-1 can induce production of IL-10 in naïve B cells ( 55 ) and stimulate the differentiation of Breg cells ( 56 ) Additionally, B cells bind SEA and internalize it, leading to a 3-fold upregulation in the production of IL-10 ( 55 ). Bregs have been implicated as important players in autoimmunity ( 57 ), and helminth infections have been shown to affect their function in autoimmunity, potentially altering the course of disease ( 58 ). Therefore, stimulation of these cells by S. mansoni products warrants further investigation.…”
Section: Schistosoma Mansonimentioning
confidence: 99%